Efficacy of a retention pond in treating stormwater nutrients and sediment. (25th March 2021) - Nayeb Yazdi, Mohammad; Scott, Durelle; Sample, David J.; Wang, Xixi
Abstract: Urban retention ponds are a common stormwater control measure (SCM), particularly in rapidly developing coastal areas due to their physiography. A retention pond can hold a large percentage of its inflow for a period of time and then gradually release it, allowing suspended sediments and attached pollutants to settle out and enabling biological and physicochemical processes (e.g., uptake or adsorption), reducing pollutant concentrations. On the other hand, retention ponds can also become a source of pollutants resuspended or mobilized from bottom sediments. This study instrumented a retention pond located in a mid-Atlantic coastal city to monitor inflows and outflows for a one-year period. The pond was not designed to provide water quality treatment, so no forebay or multiple-outlets are present, thus this pond may represent a baseline condition. The results indicated that during colder months (defined as the average temperature < 15 °C), the pond reduced total suspended sediments (TSS) and phosphorus (P) by 62% and 10%, respectively, but it exported nitrogen (N), increasing the outflow N concentration by 8%. During warm weather, the pond's treatment efficiency improved, with an average TSS reduction of 75% and the N and P reductions of 47% and 10%, respectively. This increased treatment effectiveness is probably caused by the more active biological activities (e.g., nitrification and denitrification) during the warmer months. A Storm Water Management Model (SWMM) model was parameterized and calibrated to simulate the pond. The model simulated TSS and total P (TP) treatment reasonably well, but less so for total N (TN) treatment, and depended on the season. Modeling could extend the reach of the assessment of performance beyond the limit of a one-year monitoring study. Additional research is suggested to better understand the dynamics and predictability of biogeochemical processes within ponds, particularly for N. Graphical abstract: Image 1 Highlights: We chose an older, ordinary retention pond in coastal Virginia, USA for a monitoring study. We assessed total suspended sediment (TSS), nitrogen (N) and phosphorus (P). The performance of the pond during cold and warm weather was different. N was exported during the cool season; but was reduced during the warm season. SWMM was able to simulate TSS and Total P (TP) removal reasonably well.